It’s about TIME – Gal-9 as a potential immunotherapeutic target in pancreatic ductal adenocarcinoma - Knickmeier, Christin; Noubissi Nzeteu, Gaetan Aime; Gibbs, Bernhard F.; Hoogwater, Frederik J. H.; Nijkamp, Maarten W.; Bockhorn, Maximilian; Meyer, N. Helge (Frontiers in Immunology, 2025)
Pancreatic ductal adenocarcinoma (PDAC) remains one of the most lethal malignancies, characterized by an extremely poor prognosis and limited therapeutic options. Central to the progression and immune evasion of PDAC is the tumor (immune) microenvironment (TIME), where immune checkpoint proteins such as galectin-9 (Gal-9) play pivotal roles. Gal-9 significantly contributes to the immunosuppressive milieu of PDAC by interacting with various immune cells, such as T cells, macrophages, and myeloid-derived suppressor cells (MDSCs). These interactions suppress anti-tumor immunity, thus facilitating tumor growth and metastasis. This review comprehensively examines the multifaceted role of Gal-9 in the TIME of PDAC, detailing its mechanisms of action, including the induction of regulatory T cells, polarization of tumor-associated macrophages, and modulation of apoptotic pathways via Tim-3 and caspase activation. The therapeutic potential of targeting Gal-9, either alone or in combination with other immune checkpoint inhibitors such as anti-PD-L1, is also discussed, highlighting preclinical findings that suggest promising avenues for enhancing anti-tumor immune responses. By elucidating the complex biological activities of Gal-9 and its interactions within the TIME, this review underscores the importance of innovative therapeutic strategies aimed at mitigating the immunosuppressive effects of Gal-9 in PDAC.